2012
DOI: 10.1039/c2jm15173a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient blue electroluminescence of silylene-bridged 2-(2-naphthyl)indole

Abstract: We synthesised 12,12-diisopropyl-7-methyl-12H-indololo[3,2-d]-naphtho [1,2-b][1]silole from 1-bromo-2-naphthol via four steps. The silylene-bridged 2-(2-naphthyl)indole exhibited intense blue photoluminescence in solution and in the solid state. For example, the fluorescence maximum of the powder appeared at 476 nm with a high quantum yield (F ¼ 0.70). The organic light-emitting device using the silylene-bridged indole as a light-emitting layer demonstrated a high current efficiency of 3.80 cd A À1 and a power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…53 Meanwhile, silicon-bridged biaryls can serve as key components of not only light-emitting devices, but also FET, 7 solar cells, 8 and solid fluorescent sensors. 9 Hence, the application of our designed silicon-bridged biaryls to charge transporting and sensing devices is also planned.…”
Section: Resultsmentioning
confidence: 99%
“…53 Meanwhile, silicon-bridged biaryls can serve as key components of not only light-emitting devices, but also FET, 7 solar cells, 8 and solid fluorescent sensors. 9 Hence, the application of our designed silicon-bridged biaryls to charge transporting and sensing devices is also planned.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where devices containing metalloles and metallafluorenes were prepared and properties measured, generally only one or two configurations are described in a report and there does not seem to be an effort to maximize the performance of the device. There are exceptions to this observation, of course, including the study by Marks and co-workers [77c], and another example appeared in a recent report on silylene-bridged 2-(2-naphthyl)indole [79].…”
Section: Summary and Future Directionsmentioning
confidence: 97%
“…Gratifyingly, indoles 21 were a novel class of compounds and were intensely blue emissive, particularly in the solid state [28]. Subsequently, we studied extensively the crystal structures, photophysical properties, redox properties, and molecular orbitals of 21 , and concluded that 3,2′‐diorganosilylene‐bridged 2‐arylindoles, including naphthyl derivatives 22 , have great potential as blue emitters for application to EL devices [29]. Since the chemistry of 21 was previously reported,[30] this section focuses on the properties and applications of 22 .…”
Section: Organic Chromophores Based On 12h‐indololo[32‐d]naphtho[12mentioning
confidence: 99%
“…Because 22 exhibited high efficiency of fluorescence as a powder and in a doped PMMA film, we examined the performances of EL devices in which 22a was used as an emitting layer (EML; device I ) and a dopant in a host material (devices II – IV ) [29]. The structures of the devices are shown in Figure .…”
Section: Organic Chromophores Based On 12h‐indololo[32‐d]naphtho[12mentioning
confidence: 99%
See 1 more Smart Citation